Peran Program Buku Bicara (BUBI) dalam Penguatan Literasi Anak Usia Dini di Layanan Ruang Anak Perpustakaan Proklamator Bung Hatta - Monika, Putri; Rahmah, Elva; Marlini, Marlini (TSAQOFAH, 2026)
The Program Buku Bicara (BUBI) is a creative literacy service innovation by the Agen Perubahan (AP) 2025 of the Proklamator Bung Hatta Library Technical Implementation Unit (UPT), developed to enhance early childhood literacy through interactive storytelling activities in the library setting. This study aimed to describe the implementation of the BUBI Program, the role of librarians, children’s responses, and the benefits and challenges that emerged during its implementation. A qualitative descriptive method was employed, with data collected through observation, interviews, and documentation conducted during the internship (PKL) period, particularly from September to November 2025. The findings show that the BUBI Program was implemented in a structured manner and succeeded in capturing children’s attention through question-and-answer sessions and story-based interactions, thereby contributing to improved comprehension of story content, vocabulary development, and strengthened children’s confidence in communication. The main challenges encountered were related to declining child focus over certain activity durations and the limited availability of supporting media. This study concludes that the BUBI Program is effective as a creative literacy strategy in the library, with implications for the need to strengthen supporting facilities and provide storytelling training for librarians in order to further optimize the quality of children’s literacy services.